Host-Virus Interaction in Ribonucleic Acid Bacteriophage-Infected Escherichia coli: I. Location of “Late” MS2-Specific Ribonucleic Acid Synthesis - Haywood, Anne M. (1969)
When actinomycin-treated, MS2-infected Escherichia coli are labeled during a brief period later than 16 min after infection, the newly synthesized MS2 ribonucleic acid (RNA) appears first in the 30,000 × g sediment, probably bound to fragments of bacterial membranes, since the radioactivity can be released from the sediment with deoxycholate or urea. With longer labeling times, radioactivity also appears in the 30,000 × g supernatant fluid. While on the membrane, the RNA is organized into particles with sedimentation coefficients of 40, 32, and 27S in the presence of low Mg(2+). In the presence of high Mg(+), MS2-specific RNA is found in polyribosomes. These data are interpreted to mean that MS2-specific RNA is synthesized and organized into larger structures on membrane. More than 8 min of labeling is required before radioactivity is found in the 81S virion which appears in the supernatant fluid.